Where is an emotion? Greater interference in a gut-focused visceroception group undertaking an emotional stop-signal task. (April 2022) - Davey, Steven; Halberstadt, Jamin; Bell, Elliot
Abstract: The external environment demands attention, inhibiting attention to one's internal environment (including visceral awareness, or "visceroception"). The role of visceral awareness in emotional experience has been widely investigated, with findings including increased emotional intensity and capacity for emotion regulation with increased visceroceptive ability. However, much subtle and rapid visceral activity may go unnoticed. The current study is part of a wider exploratory project seeking to mitigate the tendency to orient outwardly – in line with other studies on interoception, meditation and mindfulness – but comparing specific visceral systems: the heart and gastrointestinal tract. In so doing, the possibility of emotional localisation was explored. The current study identified differences in interference between groups using a stop-signal task following a visceroceptive intervention. The findings support a localized effect, in which the gastroception group displayed slower reaction times and increased stopping ability. The gastrointestinal tract may be important to address in future studies of interoception and emotion. Highlights: The external environment inhibits attention to bodily responses, including emotional. Participants were trained to focus on their chest or lower abdomen. They undertook an emotional "Stop-Signal Task" to assess change in inhibition. The abdomen group results suggest greater interference and disinhibition. This result may imply 'emotional localisation' in the gastrointestinal tract.